2006
DOI: 10.1103/physreve.74.031501
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric study of the antiplasticization of trehalose by glycerol

Abstract: Recent measurements have suggested that the antiplasticizing effect of glycerol on trehalose can significantly increase the preservation times of proteins stored in this type of preservative formulation. In order to better understand the physical origin of this phenomenon, we examine the nature of antiplasticization in trehalose-glycerol mixtures by dielectric spectroscopy. These measurements cover a broad frequency range between 40 Hz to 18 GHz (covering the secondary relaxation range of the fragile glass-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(123 citation statements)
references
References 81 publications
8
113
2
Order By: Relevance
“…Glycerol exerted antiplasticizing effect on the local motions in trehalose only below a critical temperature. 77 This critical temperature was found to be inversely related to the glycerol concentration. Thus, at lower glycerol concentrations, antiplasticization would occur at higher temperatures.…”
Section: Effect Of Additives On Secondary Relaxationsmentioning
confidence: 92%
“…Glycerol exerted antiplasticizing effect on the local motions in trehalose only below a critical temperature. 77 This critical temperature was found to be inversely related to the glycerol concentration. Thus, at lower glycerol concentrations, antiplasticization would occur at higher temperatures.…”
Section: Effect Of Additives On Secondary Relaxationsmentioning
confidence: 92%
“…The impact of low-molecular weight diluents on the antiplasticization and plasticization was extensively investigated by experimental techniques probing the dynamics in the glassy state, such as inelastic neutron scattering [39,87,104,105] and dielectric spectroscopy (DES) [42,43] but also by molecular dynamics simulations [87][88][89]. These studies have mostly focussed on the trehalose-glycerol system, which is of relevance for the stabilization of sensitive pharmaceutical proteins.…”
Section: Relation To Sub-t G Relaxationsmentioning
confidence: 99%
“…These dynamic modes and their relation to pharmaceutical stability have primarily been explored for trehalose [34,39]. Using techniques, such as neutron scattering [39] and dielectric spectroscopy (DES) [40][41][42][43], it was observed that several of the dynamic modes in the glassy matrices could be partly suppressed or slowed down by the addition of limited amounts of a low-molecular weight hydrogen-bond forming diluent, such as glycerol or sorbitol. This phenomenon was identified as the antiplasticization of the matrix by the diluent [39,44].…”
Section: Introductionmentioning
confidence: 99%
“…Arginine being a strongly basic residue is typically found on the surface of a protein when immersed in water. However, when it is immersed in trehalose [75], a solvent less polar than water, Arginine tends to reduce the area of contact. The behavior of neutral residues however depends strongly on their spatial neighbors.…”
Section: Protein Structurementioning
confidence: 99%